2016
DOI: 10.1155/2016/5396439
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigations and DFT Calculations on 3-(Diacetylamino)-2-ethyl-3H-quinazolin-4-one

Abstract: The theoretical and experimental vibrational frequencies of 3-(diacetylamino)-2-ethyl-3H-quinazolin-4-one (2) were investigated. The experimental Laser-Raman spectrum (4000–100 cm−1) and FT-IR spectrum (4000–400 cm−1) of the newly synthesized compound were recorded in the solid phase. Both the theoretical vibrational frequencies and the optimized geometric parameters such as bond lengths and bond angles have for the first time been calculated using density functional theory (DFT/B3LYP and DFT/M06-2X) quantum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The investigation reported here involves the synthesis, experimental and theoretical vibrational analysis of ( E )-1-(4-methoxyphenyl)-5-methyl- N ′-(3-phenoxybenzylidene)-1 H -1,2,3-triazole-4-carbohydrazide ( 2 ) as a continuation of our work in the field [ 20 , 21 , 22 , 23 ]. Of particular interest is the agreement between the theoretical results obtained and the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation reported here involves the synthesis, experimental and theoretical vibrational analysis of ( E )-1-(4-methoxyphenyl)-5-methyl- N ′-(3-phenoxybenzylidene)-1 H -1,2,3-triazole-4-carbohydrazide ( 2 ) as a continuation of our work in the field [ 20 , 21 , 22 , 23 ]. Of particular interest is the agreement between the theoretical results obtained and the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…For heteronuclear aromatic compounds, the CC stretching vibrational bands were observed the narrow ranges of 1,600–1,585 and 1,500–1,400 cm −1 . [ 26,28 ] In this study, the CC stretching vibrations in the ring were theoretically found at 1,565, 1,542, 1,274, 1,264, 1,026, and 1,024 cm −1 with the aforementioned computational method. These stretching modes were assigned at 1,582/1,568, 1,532/1,549, 1,300/1,285 (for two band), and 1,038/1,025 cm −1 (for two band) in the FT‐IR/Laser‐Ra spectrum, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…Besides, the C-C stretching modes and C-C-C ring vibration bands have been found in the ranges from 1600 cm -1 to 1585 cm -1 and 1500 cm -1 to 1400 cm -1 [34,35]. At the same time, the other aromatic stretching mode of C-N bands in the side chains always occurs with the other aromatic stretching bands and bending modes together.…”
Section: Resultsmentioning
confidence: 99%